Treating status epilepticus in the community. Issue 17 (4th September 2015) - Shah, Apeksha; Kelso, Andrew
<x xml:space="preserve">Abstract</x> Early treatment of status epilepticus is vital so it is important to identify those patients at risk. Carers can then be trained to use buccal midazolam where possible for early intervention.